2020
DOI: 10.1177/0891243219897062
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Increases in Sex with Same-Sex Partners: Do Trends Vary by Gender, Race, and Class?

Abstract: We examine change across U.S. cohorts born between 1920 and 2000 in their probability of having had sex with same-sex partners in the last year and since age 18. Using data from the 1988–2018 General Social Surveys, we explore how trends differ by gender, race, and class background. We find steep increases across birth cohorts in the proportion of women who have had sex with both men and women since age 18, whereas increases for men are less steep. We suggest that the trends reflect an increasingly accepting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The estimates for those who identify as gay or bisexual are slightly larger here compared to the proportion of people who identify as gay or bisexual in the United Kingdom and Australia (see Geary et al 2018;Richters et al 2014); however, this is to be expected with a younger sample, as NSFG only sampled Americans aged 15-45 while the United Kingdom sampled adults aged 16-74 and Australia sampled adults aged 16 -69. Indeed, many studies show that younger individuals are more likely to identify as non-heterosexual compared to older individuals (see Bridges and Moore 2018;England et al 2016;Mishel et al forthcoming). Table 1 also shows that there are many gender differences when assessing how men and women age 15-45 label their sexual orientation: significantly more women than men identify as bisexual, and significantly more men than women identify as gay.…”
Section: Resultsmentioning
confidence: 99%
“…The estimates for those who identify as gay or bisexual are slightly larger here compared to the proportion of people who identify as gay or bisexual in the United Kingdom and Australia (see Geary et al 2018;Richters et al 2014); however, this is to be expected with a younger sample, as NSFG only sampled Americans aged 15-45 while the United Kingdom sampled adults aged 16-74 and Australia sampled adults aged 16 -69. Indeed, many studies show that younger individuals are more likely to identify as non-heterosexual compared to older individuals (see Bridges and Moore 2018;England et al 2016;Mishel et al forthcoming). Table 1 also shows that there are many gender differences when assessing how men and women age 15-45 label their sexual orientation: significantly more women than men identify as bisexual, and significantly more men than women identify as gay.…”
Section: Resultsmentioning
confidence: 99%
“…The difficulty of distinguishing age-period-cohort effects is well documented in existing literature (Yang and Land 2013). Following Mishel et al (2020), I included respondents' birth cohort and age, but not survey year (i.e., period), in all models. 3 This means the cohort trends reported here may partly reflect period effects.…”
Section: Analytic Strategymentioning
confidence: 99%
“…I used multiple binary logit regression models for different systems of financial management instead of multinomial logistic regression models, due to smaller cell sizes in the latter (Mishel et al 2020). Nonetheless, alternative multinomial models yielded substantively consistent results.…”
Section: Analytic Strategymentioning
confidence: 99%
“…In the US, the increase in the proportion of people identifying as lesbian, gay, bisexual, or transgender reported by Newport (2018) was wholly driven by increasing identification in younger cohorts. Analysing sexual behaviour data from the US General Social Survey, Mishel et al (2020) found strong cohort differences in same-sex sexual behaviour, with younger cohorts far more likely to report this behaviour. The cohort increase was greater for women than men.…”
Section: Identification Changementioning
confidence: 99%